Nutrigenomics and Parkinson's disease - Razali, Khairiah; Algantri, Khaled; Loh, Su Peng; Cheng, Shi-Hui; Mohamed, Wael Mohamed Yousef (Elsevier, 2024)
Parkinson’s disease (PD) is a multifactorial disease, the development, and progression of which are influenced by multiple factors, including the genetic markups and the environment. Nutrition is considered one of the most robust environmental factors affecting PD as it can either induce or reduce disease susceptibility. Epigenetic mechanisms regulate gene expression through DNA methylation, histone modifications, and noncoding RNAs (ncRNAs) activity. Accumulating evidence from nutriepigenomics studies has reported altered epigenetic mechanisms in clinical and preclinical PD models and the potential role of nutrition in modifying the changes. In addition, through nutrigenetics and nutrigenomics studies, the diet-gene, and gene-diet interactions in relation to PD development and progression have been investigated. Herein, current findings on the roles of nutrition in epigenetic mechanisms underpinning PD development and progression are discussed. Besides, the potential of the personalized nutrition approach as adjuvant therapy for PD are also underlined.